The Coastal Streamflow Flux in the Regional Arctic System Model - Hamman, J.; B. Nijssen; A. Roberts; A. Craig; W. Maslowski; R. Osinski (Zenodo, 2017)
The Arctic coastal streamflow flux is an important driver of dynamics in the coupled ice-ocean system. We have developed a new streamflow routing model (RVIC), coupled within the Regional Arctic System Model (RASM), to simulate the coastal freshwater flux. RASM is a high-resolution regional Earth system model applied over a Pan-Arctic model domain. This dataset includes distributed daily coastal streamflows between 1979 and 2014 for the RASM domain. In Hamman et al. (2017) we demonstrate the performance of RASM and RVIC-simulated streamflow in fully coupled model simulations and discuss the improvements this derived dataset has, relative to existing distributed datasets in the Arctic. See the following references for further details on this dataset: Hamman, J., B. Nijssen, A. Roberts, A. Craig, W. Maslowski, and R. Osinski, 2017: The Coastal Streamflow Flux in the Regional Arctic System Model. Journal of Geophysical Research: Oceans, doi:10.1002/2016JC012323. Hamman, J., B. Nijssen, M. Brunke, J. Cassano, A. Craig, A. DuVivier, M. Hughes, D.P. Lettenmaier, W. Maslowski, R. Osinski, A. Roberts, and X. Zeng, 2016: Land surface climate in the Regional Arctic System Model. Journal of Climate, doi:10.1175/JCLI-D-15-0415.1.